Secan²x + tan² = Secan⁴x - tan⁴x
Answers
Answered by
1
Explanation:
In trigonometry:
sec²A = 1 + tan²A → sec²A - tan²A = 1
In question, RHS:
→ sec⁴x - tan⁴x
→ (sec²x)² - (tan²x)²
→ (sec²x - tan²x)(tan²x + sec²x)
→ 1(sec²x + tan²x)
→ sec²x + tan²x
Hence proved.
Answered by
0
here is your answer. jskxbkaabzhzhxvnasbxbsjkzjxnwmsk
Attachments:
![](https://hi-static.z-dn.net/files/d26/71725b6ae0c4d65a4ca61e788d8abc14.jpg)
Similar questions
Social Sciences,
5 months ago
Math,
5 months ago
Social Sciences,
5 months ago
Math,
10 months ago
Social Sciences,
10 months ago